1992
DOI: 10.1128/mcb.12.5.2078
|View full text |Cite
|
Sign up to set email alerts
|

Control of formation of two distinct classes of RNA polymerase II elongation complexes.

Abstract: We have examined elongation by RNA polymerase II initiated at a promoter and have identified two classes of elongation complexes. Following initiation at a promoter, all polymerase molecules enter an abortive mode of elongation. Abortive elongation is characterized by the rapid generation of short transcripts due to pausing of the polymerase followed by termination of transcription. Termination of the early elongation complexes can be suppressed by the addition of 250 mM KCI or 1 mg of heparin per ml soon afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
237
0
8

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(256 citation statements)
references
References 93 publications
11
237
0
8
Order By: Relevance
“…As demonstrated by the examples in Figure 2A, in the production of mRNA a major restriction point occurs shortly after Pol II initiates. The polymerase becomes stably engaged by elongating the nascent transcript past about 12 nt and then comes under the control of factors that significantly slow or halt elongation (16). These promoter proximately paused polymerases are the major form of polymerase found bound to metazoan chromosomes and are poised for entry into productive elongation (9,17).…”
Section: Promoter Proximally Paused Polymerasesmentioning
confidence: 99%
See 1 more Smart Citation
“…As demonstrated by the examples in Figure 2A, in the production of mRNA a major restriction point occurs shortly after Pol II initiates. The polymerase becomes stably engaged by elongating the nascent transcript past about 12 nt and then comes under the control of factors that significantly slow or halt elongation (16). These promoter proximately paused polymerases are the major form of polymerase found bound to metazoan chromosomes and are poised for entry into productive elongation (9,17).…”
Section: Promoter Proximally Paused Polymerasesmentioning
confidence: 99%
“…In vitro transcription experiments initially provided the tools to identify both the positive and negative factors involved in controlling the elongation phase of transcription (16). A key feature of transcription of virtually any promoter in vitro using a crude nuclear extract is the inhibition of the generation of long transcripts by the ATP analog 5,6-Dichloro-1-β-Dribofuranosylbenzimidazole (DRB) (16,22). P-TEFb (23), NELF (19) and DSIF (18) were purified based on their activities during reconstitution of DRB-sensitive transcription using fractionated nuclear extracts.…”
Section: Promoter Proximally Paused Polymerasesmentioning
confidence: 99%
“…The drug 5,6-dichloro-lb-D-furanosylbenzimidazole (DRB) was shown to inhibit production of transcripts elongating past the site of premature transcriptional termination in the c-myc gene in microinjected Xenopus oocytes; DRB had no effect on production of prematurely terminated transcripts, thus revealing two classes of transcription complex . Similarly, by analyzing transcriptional elongation on cloned templates in Drosophila cell extracts, Marshall and Price (1992) have identified two classes of elongation complex. Productive elongation complexes generating full length transcripts were shown to derive from early paused complexes by the action of a factor called P-TEF, which is inhibited by DRB (Kephart et al, 1992;Marshall and Price, 1992).…”
Section: Regulation Of Transcriptional Elongation Within Eukaryotic Cmentioning
confidence: 99%
“…Similarly, by analyzing transcriptional elongation on cloned templates in Drosophila cell extracts, Marshall and Price (1992) have identified two classes of elongation complex. Productive elongation complexes generating full length transcripts were shown to derive from early paused complexes by the action of a factor called P-TEF, which is inhibited by DRB (Kephart et al, 1992;Marshall and Price, 1992). It was suggested that regulatory proteins could influence transcriptional elongation by enhancing the activity of P-TEF or a similar cellular factor.…”
Section: Regulation Of Transcriptional Elongation Within Eukaryotic Cmentioning
confidence: 99%
“…The nucleoside analog DRB (5,6-dichloro-1-b-Dribofuranosylbenzimidazole) is another transcriptional inhibitor, which like ARC, targets the elongation stage of transcription by inhibiting the positive transcription elongation factor b (P-TEFb, a complex of Cdk9/cyclin T1) (Marshall and Price, 1992). Previously, we had demonstrated that though ARC and DRB repressed transcription to a similar extent, ARC induced more potent apoptosis in a colon cancer cell line (Radhakrishnan and Gartel, 2006b).…”
mentioning
confidence: 99%